Diogenes matabiru, a new species of hermit crab from Lombok Island, Indonesia (Crustacea, Decapoda, Anomura, Diogenidae) - Rahayu, Dwi Listyo; Pratiwi, Rianta (Zootaxa, 2022)
A new species of hermit crab, Diogenes matabiru, is described and illustrated on the basis of the specimens collected from mangrove environment in the eastern Lombok Island, Indonesia. This new species is related to D. pallescens Whitelegge, 1897 but differs in the shape of cheliped, telson and coloration in life. A key to the species of the genus Diogenes from Indonesia is also provided.